Case Report: Two cases of adrenal anastomosing hemangioma misdiagnosed as angiosarcoma - He, Dong-Lin; Feng, Run-Lin; Guo, Xin; Ke, Chang-Xing (Frontiers in Oncology, 2025)
Anastomosing hemangioma (AH) is a benign vascular tumor that has gradually been recognized in recent years, initially identified in the genitourinary tract. AH located in the adrenal gland is extremely rare, and the atypical preoperative symptoms and imaging findings, as well as the postoperative pathological differential diagnosis, often lead to misdiagnosis. We herein report two case of adrenal AH that was misdiagnosed as adrenal angiosarcoma and review the relevant literature.